De Gruyter Handbook of Citizens' Assemblies - Reuchamps, Min; Vrydagh, Julien; Welp, Yanina (Citizens' Assemblies and Mini-Publics, 2023)
The De Gruyter Handbook of Citizens' Assembly showcases the state of the art of Citizens'asembly and opens new perspectives informed by multidisciplinary research and new thinking about deliberative participatory processes.